Reversal of immune complex inhibition of antibody-dependent cell-mediated cytotoxicity by normal human serum. - Isturiz, M A (1982)
The results of this study demonstrate that inhibition of antibody-dependent cell-mediated cytotoxicity (ADCC) of human peripheral blood mononuclear cells (PBMC) by ovalbumin (OA)-IgG anti-OA immune complexes (IC) can be reversed by normal human serum (NHS) or serum from a patient with congenital deficiency of the second component of complement (C2 def-HS) lacking activity of the classical complement (C) pathway. On the other hand, NHS that had been inactivated by heating at 56 degrees C for 30 min (HI-NHS) or NHS depleted of the alternative C pathway activity by absorption with zymosan (Zy-NHS) did not restore the ADCC of IC-blocked PBMC. These results suggest that the alternative pathway of C plays a very important role in the re-establishment of ADCC of PBMC blocked with IC. The recovered activity was susceptible to a new inhibition when re-exposed to IC, demonstrating that the NHS effect depends on the recovery of the functional activity of the receptor for the FC fragment of IgG on PBMC and not on the induction of non-specific cytotoxicity. The ability of NHS to restore the cytolytic potential of IC-inhibited PBMC was dependent on the time of exposure of PBMC to IC before the addition of the unblocking agent (NHS). After prolonged reaction of PBMC with IC, the blocked cells were unable to recover their ADCC activity by incubation with NHS. Unblocking of the Fc receptor of PBMC by C may be a physiological way to prevent permanent impairment of the immune mechanisms that depend on its function in the free state.